2021
DOI: 10.1007/s44177-021-00004-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Degradation by Invasive Alien Plants in the Anthropocene: Challenges and Prospects for Sustainable Restoration

Abstract: Biodiversity, soil, air, and water are the vital life-supporting systems of this planet Earth. However, the deliberate and accidental introduction of invasive alien plants (IAPs) in the Anthropocene majorly due to the global international trade perturbed the homeostasis of our biosphere. IAPs are considered as one of the major drivers of biodiversity loss and ecosystem degradation. The pervasive threats of IAPs to environmental sustainability and biosecurity are further exacerbated under the COVID-19 pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 178 publications
0
28
0
Order By: Relevance
“…In this section, soil degradation and its restoration by plants and mushrooms (Figure 10) are discussed. There are many human activities that lead to soil degradation all over the world; for example, in the European Mediterranean region [134], chemical degradation resulting from heavy metals in China [137], waterlogging and soil salinity in India [138], or pesticides [139], physical degradation resulting from soil compaction [140], or environmental degradation due to invasive alien plants [141]. Several studies have been reported about different strategies for remediation of pollutants or other causes of soil degradation, which differ using plants or mushrooms.…”
Section: Soil Restoration By Plants and Mushroomsmentioning
confidence: 99%
“…In this section, soil degradation and its restoration by plants and mushrooms (Figure 10) are discussed. There are many human activities that lead to soil degradation all over the world; for example, in the European Mediterranean region [134], chemical degradation resulting from heavy metals in China [137], waterlogging and soil salinity in India [138], or pesticides [139], physical degradation resulting from soil compaction [140], or environmental degradation due to invasive alien plants [141]. Several studies have been reported about different strategies for remediation of pollutants or other causes of soil degradation, which differ using plants or mushrooms.…”
Section: Soil Restoration By Plants and Mushroomsmentioning
confidence: 99%
“…The nutrient discrepancy in the plant is a common occurrence found in degraded land, and among different plant nutrients, iron is the essential ingredient for plant growth (Connorton et al, 2017 ). Rapid industrialization, urbanization, unsuitable land use (IPBES, 2018 ), fast agricultural practices (Keesstra et al, 2018 ), soil salinization (Edrisi et al, 2021 ), soil erosion (Paul et al, 2020a , b ), invasion of alien species (Rai, 2021 ), poor governance management strategy (Gerber et al, 2014 ), overexploitation of natural resources, excessive mining (Upadhyay and Edrisi, 2021 ; Shakeel et al, 2022 ), etc., degrade more than 33% of global land resources through direct and indirect approaches (IPBES, 2018 ; Srinivasarao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the fast spread of T. diversifolia could devastate the environment and have an impact on the community's socio-economic and livelihood prospects (WITT ET AL., 2019). The landscape selected in this study (Aizawl, Mizoram, North East India) is of extreme ecological and socio-economic relevance as it is an integral landscape within the Indo-Burma biodiversity hotspot (RAI, 2012(RAI, , 2015(RAI, , 2022RAI & SINGH, 2021). Nevertheless, in India, a comprehensive study on T. diversifolia is limited and negligible especially in the context of a biodiversity rich region i.e.…”
Section: Introductionmentioning
confidence: 99%